Great Barrier Reef blueprint for resilience - (:unkn) unknown (Great Barrier Reef Marine Park Authority, 2017)
[Extract] This Blueprint signals a change in the future management of the Great Barrier Reef ... This Blueprint has been shaped by the outcomes of the Great Barrier Reef Summit, backed by the knowledge, experience and unwavering commitment of the dedicated individuals at the Great Barrier Reef Marine Park Authority and our many partners ... This Blueprint is not intended to be a ‘plan’, but rather to present the 10 most promising initiatives — based on our collective experience, knowledge and best available information — to protect the Reef and build resilience.
Often referred to as 'Blueprint' and 'Reef Blueprint'.
Keywords: Blueprints; Corporate planning; Managing Multiple Use; Corporate plans; Policies and position statements; Reef-wide